SOCIALISATION OF THE CHINESE PEOPLE LIVING IN DERRICK STREET, JOHANNESBURG - Liu, Xiaoli (My University, 2014)
This basic interpretive qualitative study is on socialisation of the Chinese people living in Derrick Street, Johannesburg. Despite the development of globalization, results from other research indicate that Chinese immigrants continue to face socialisation challenges in their host country. As the growing phenomenon of Chinese emigration to South Africa, findings of this research can be used in coming up with strategies to address the identified integration challenges. In this study, data was collected from face to face semi structured interviews. Attitude and English language competency are reported as major challenges which deter the Chinese people from integrating fully into South African communities. Given the apparent reported lack of desire to improve their English language as one of the key factor in realizing socialisation within a diverse community, this suggests that Chinese people show low interest towards integrating their daily lives into the local community. Furthermore, with the high level of crime and corruption, most of the participants reported that they do not plan to stay in South Africa permanently. In conclusion, Chinese people in Derrick Street seem to seal themselves in cocoons, exclusive from the local communities. However, this does not appear to disrupt or interfere with their daily life and business activities.
MM (P&DM) thesis
Keywords: Socialisation of people; Chinese